Relationship of Tai Yai Livelihood and Biodiversity to Traditional Knowledge - เขื่อนแก้ว, สุณี; วังภคพัฒนวงศ์, ประสิทธ์; จำปีทอง, อรุโณทัย (KKU Science Journal, 2013)
Tai Yai is an ethnic group speaking the Tai-Kradi language. Most of Tai Yai lives in the Shan state in Burma. Furthermore, there are some who live at Doi Tai laeng, at the border between Thailand and Burma. Tai Yai people have special characteristics, including their language, dress and livelihood which rely on the natural surroundings. Knowledge about this has been passed on from generation to generation for a long time. Agriculture is a typical career of Tai Yai. They have to take advantage of a variety of plants, using them, for example, for buildings, fuel, food or herbal medicine. Moreover, some plants are used in connection with traditional ceremonies. It is expected that conservation of this knowledge might lead to economic development, in particular as some species may be used as economic plants in the future.